Coordination of cell division and differentiation in plants in comparison to animals - Fehér, Attila; Magyar, Zoltán (Acta Biologica Szegediensis, 2015)
During animal and plant development all cells are originated from a single fertilized oocyte, the zygote. To generate an adult organism from the single-celled zygote many rounds of cell division are required to be completed. Cell division is manifested through a well-defined series of molecular and cellular events that is often referred as the cell cycle. Studies in various model organisms demonstrated that the eukaryotic cell cycle is regulated in a conserved manner with cyclin-dependent kinases (CDKs) in the centre. It is widely believed that cells must exit the cell cycle for cell differentiation. Accordingly, cell division and differentiation do not happen at the same time. The main questions in developmental biology are how these processes are coordinated during development, how do cells stop division before differentiation, and why and how cells maintain or re-initiate cell division activity? Recent studies indicate direct links between molecular cell cycle and cell differentiation machineries. The basic mechanisms regulating the balance between cell proliferation and differentiation are remarkably similar in plants and animals despite their fundamentally different developmental strategies. There is considerable dissimilarity, however, in the upstream signalling pathways affecting this balance in developmental and environmental contexts. In this chapter we focus our attention on the molecular regulatory mechanism controlling and coordinating cell division and differentiation both in animals and plants with emphasis on the entry and exit points of the cell cycle.